Analysis of safety items in works of the Minha Casa Minha Vida program in the municipality of Dois Vizinhos – PR - Barbosa, Eduardo Gabriel; Bassanezi, João Felipe; Starck, Ma. Keli (Seven Editora, 2023)
Occupational safety is an area of great importance in civil construction, as it is an activity of repetitive exercises, risky practices that demand a lot from the worker involved techniques and control practices were created in the civil construction work environment. There are numerous safety assessment and control techniques, among which the inspection checklist stands out, a quick and efficient way to survey and identify points of non-conformities, as well as risk areas and situations, with approaches and frequencies of use determined according to the scenario in question. In this work, the use of safety was addressed, considering inspection of Personal Protective Equipment (PPE), Collective Protection Equipment (CPE), construction site conditions, machine and tool conditions, as well as work practices employed. To this end, a checklist was developed for the application of small-scale works (OPP) of the Minha Casa Minha Vida Program (PMCMV). To verify the effectiveness and approach of the inspection checklist, 28 works were visited in the municipality of Dois Vizinhos - PR in the phases of execution of foundations, masonry survey and roofing, and then an analysis report was made. With this, it was possible to identify that safety at work in works of the Minha Casa Minha Vida Program (PMCMV) with the application of the inspection checklist reached an average of the three phases analyzed that 71.67% make use of good practices, as a result, most of the points of improvement are due to the orientation of employees to good practices of work safety. DOI:https://doi.org/10.56238/sevened2023.006-091